Recent advances in graphene-based planar micro-supercapacitors for on-chip energy storage - Wu, Zhong-Shuai; Feng, Xinliang; Cheng, Hui-Ming (National Science Review, 2014)
The current development trend towards miniaturized portable electronic devices has significantly increased the demand for ultrathin, flexible and sustainable on-chip micro-supercapacitors that have enormous potential to complement, or even to replace, micro-batteries and electrolytic capacitors. In this regard, graphene-based micro-supercapacitors with a planar geometry are promising micro-electrochemical energy-storage devices that can take full advantage of planar configuration and unique features of graphene. This review summarizes the latest advances in on-chip graphene-based planar interdigital micro-supercapacitors, from the history of their development, representative graphene-based materials (graphene sheets, graphene quantum dots and graphene hybrids) for their manufacture, typical microfabrication strategies (photolithography techniques, electrochemical methods, laser writing, etc.), electrolyte (aqueous, organic, ionic and gel), to device configuration (symmetric and asymmetric). Finally, the perspectives and possible development directions of future graphene-based micro-supercapacitors are briefly discussed.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Energy storage; Graphene; Interdigital; Mirco-supercapacitors; Planar; Supercapacitors